The health-related quality of life of Vietnamese type 2 diabetic patients - Nghiep Ke Le,; Niruwan T,; Cuong VD,; Santisith K,; Surasak T, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Type 2 diabetes is a chronic metabolic disorder that has serious complications including quality of life. This research analyses the health-related quality of life and the relative factors of type 2 diabetics in Tam Binh District, Vinh Long Province, Vietnam. A cross-sectional study was administered from July-August 2019 at seventeen communes in Tam Binh district. All total of 500 patients diagnosed type 2 diabetes and aged 35 years and older, comprised this investigation. The exploration questionnaire encompassed the Vietnamese Diabetes Quality of Life. Diabetics had an average age of 59.77 + 9.81 years. The health-related quality of life score was moderate at 60.15 + 21 points. The inter-personal relationship had the lowest score. However, the highest score was detected for the physical endurance. The significant differences could be distinguished at different individual components like age, marital status, location, family type, education, occupation, income, duration, glycaemia, HbA1c, hypoglycemia, alcohol-using, treatments, and other issues. The study highlighted that type 2 diabetes had a negative impact on health-related quality of life. Some patient characteristics affected Vietnamese diabetes quality of life score.